(untitled) (Itinera, 2017)
Contrary to a western philosophical tradition that has always favoured vision and language as synonyms of thought, the theatre of the Senses uses the memory of the body and sensorial languages to make the audience experience a crossing (internal as well as external) into the darkness of non-knowledge. In this theatre of the Night, the « passengers » (name given to the audience) take part in the action, guided by « inhabitants » (the actors) who have developed for them a sensorial journey whose each stage mobilizes the whole body in an active listening. By making their way in this manner in the dark, everybody is asked to discover in themselves a new spatiality which they will use to see and hear better, to « hear oneself see, ultra-see and ultra-hear » (Bachelard, 1957) that is to say sentir(e), word which also means listen both in Spanish and Italian and is indissociable from thinking (Damasio, 1995). A new relation to the world, concrete, non -visual and non-verbal ensues that has consequences in the all the orders of life.